Pengaruh Kulit Buah Jengkol (Phitecellobium lobatum (Jack) Prain ) terhadap Tingkat Konsumsi Makan Tikus Sawah (Rattus argentiventer (Rob & Kloss) Di Laboratorium - Maria Simbolon; Suzanna Fitriany Sitepu; Mukhtar Iskandar Pinem (Jurnal Agroekoteknologi, 2017)
ABSTRACT The Effect of dogfruit pericarp (Pithecellobium lobatum(Jack) Prain.) to consumption levels field rats (Rattus argentiventer (Rob & Kloss) in  laboratory.    Chemical control seems to be able to provide better results than other techniques, but the chemicals used can to harm other animals that are not pestst such as humans or pets, therefore the use of repelan from plant materials ie rind dogfruit  plant is expected to reduce the rat attack on the field. This research had been  conducted at the laboratory of vertebrate BBPPTP (Balai Besar Perbenihan dan Proteksi Tanaman Perkebunan) is located at Jl. Asrama Number. 124. Pondok Kelapa, Medan in november 2015 to february 2016, using a randomized block design non factorial. Parameter observed were field rats weights, food consumption levels and the behavior of field rat. The result showed that Utilitazion of dogfruit pericarp significantly reduce the rate of food consumption and weight field rats. The best result were showed by in treatment 800 g / L. Keywords: utilitazion of dogfruit pericarp,  consumption levels, and field rats